2002
DOI: 10.1098/rspb.2002.2144
|View full text |Cite
|
Sign up to set email alerts
|

Filial cannibalism improves survival and development of beaugregory damselfish embryos

Abstract: Cannibalism of small numbers of offspring by a parent has been proposed as an adaptive parental strategy, by providing energy to support parental care. However, there are few empirical studies to support this hypothesis. We conducted field and laboratory experiments to investigate partial filial cannibalism in Stegastes leucostictus, a coral reef fish with paternal care. Partial cannibalism was shown to be common, and males were found to remove developing embryos from throughout a clutch in a random pattern, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 53 publications
1
76
1
Order By: Relevance
“…One study suggested that energy from partial clutch cannibalism could potentially offset costs related to care (Apogon lineatus; Kume et al 2000), while another claimed that energy from eggs would be insufficient (G. aculeatus;Smith 1992). Also inconsistent with the energy-based hypothesis, Payne et al (2002) found that filial cannibalism increases in the later stages of egg development, when egg energetic value is much lower. Thus, there is a lack of general support for the energy-based explanation of filial cannibalism (Rohwer 1978;Sargent 1992), and at best current theory can only explain cannibalism in some cases.…”
contrasting
confidence: 41%
“…One study suggested that energy from partial clutch cannibalism could potentially offset costs related to care (Apogon lineatus; Kume et al 2000), while another claimed that energy from eggs would be insufficient (G. aculeatus;Smith 1992). Also inconsistent with the energy-based hypothesis, Payne et al (2002) found that filial cannibalism increases in the later stages of egg development, when egg energetic value is much lower. Thus, there is a lack of general support for the energy-based explanation of filial cannibalism (Rohwer 1978;Sargent 1992), and at best current theory can only explain cannibalism in some cases.…”
contrasting
confidence: 41%
“…Indeed, previous work suggests that a range of factors are likely to affect and favour the evolution of filial cannibalism (Manica 2002;Payne et al 2002;Neff 2003;Klug & Bonsall 2007). For example, both parental condition and density-dependent egg survival affect filial cannibalism in the sand goby (Klug et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Because energy is such an obvious benefit of filial cannibalism, much of the work aimed at understanding the adaptive significance of filial cannibalism has focused on energetic benefits (reviewed in Manica 2002). However, some have suggested that energetic benefits alone are unlikely to explain the prevalence of filial cannibalism in natural systems (Smith 1992;Payne et al 2002;Klug et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, parental care is more common in the former than in the latter group [27] and a variety of parental care strategies directly improve the access of O 2 to the embryos. For example, parents may choose nest sites according to O 2 availability [28,29], fan their eggs to improve suboptimal O 2 conditions [30,31], increase nest opening size [32,33] or cannibalize some of the eggs to improve the oxygenation of the remaining embryos [34,35]. In fact, parental care in aquatic species may have evolved, at least partially, to protect developing embryos from low O 2 availability, which in turn could have favoured the evolution of larger egg sizes [6,36].…”
Section: Introductionmentioning
confidence: 99%